THE IMPACT OF SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH BRAND IMAGE IN MINIMARKETS - Adrifa, Zacky Putra; Mariam, Siti; Sutawijaya, Ahmad Hidayat; Ramli, Abdul Haeba (Yayasan Education and Social Center, 2025)
Minimarkets are still the primary choice for shopping for daily necessities for all levels of Indonesian society. This study aims to examine the impact of service quality on customer loyalty through brand image at Indomaret minimarkets. The method used in this study is quantitative. Data measurement in this study was carried out by distributing questionnaires online and face-to-face through the Google Form application and distributing questionnaires directly. Respondents in this study were aged 18-50 years and made at least 2 purchases per month. The research sample was taken using a purposive sampling technique, and totaled 174 respondents. The data analysis technique used was Partial LeastMinimarkets are still the primary choice for shopping for daily necessities for all levels of Indonesian society. This study aims to examine the impact of service quality on customer loyalty through brand image at Indomaret minimarkets. The method used in this study is quantitative. Data measurement in this study was carried out by distributing questionnaires online and face-to-face through the Google Form application and distributing questionnaires directly. Respondents in this study were aged 18-50 years and made at least 2 purchases per month. The research sample was taken using a purposive sampling technique, and totaled 174 respondents. The data analysis technique used was Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that brand image had a positive effect on customer loyalty, service quality had a positive effect on customer loyalty, and service quality had a positive effect on customer loyalty through brand image Square-Structural Equation Modeling (PLS-SEM). The results showed that brand image had a positive effect on customer loyalty, service quality had a positive effect on customer loyalty, and service quality had a positive effect on customer loyalty through brand image.